MANAJEMEN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU STUDI KASUS DI SDN BOJONGPICUNG 2 KABUPATEN CIANJUR DAN SDN CIBABAT MANDIRI 2 KOTA CIMAHI - Ade Tutty Rokhayati Rosa; Dadang Suhardiman; Indra Eka Permana; Sri Mulyani; Wildan Abdillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the management of principal supervision in improving teachers' pedagogical competence at SDN Bojongpicung 2, Cianjur Regency and SDN Cibabat Mandiri 2, Cimahi City. This qualitative descriptive research involved 20 teachers, two principals, and 152 students from grades IV-VI as research subjects. Data collection techniques used observation, interviews, and documentation. Data analysis used the Miles and Huberman model including data reduction, data display, and conclusion drawing. The results showed that supervision management includes four stages: planning, organizing, implementation, and evaluation. Planning involves needs analysis and program preparation. Organizing includes determining supervision approaches and scheduling. Implementation is carried out through clinical supervision, classroom observation, and reflective discussion using collaborative, directive, and non-directive approaches. Evaluation is conducted periodically to measure supervision effectiveness. The implementation of supervision management shows significant improvement in teachers' pedagogical competence with an average N-Gain of 0,68 in the medium to high category. The success of supervision is supported by transformational leadership, collaborative culture, and constructive feedback.